Insights Into Human Development and Disease From Human Pluripotent Stem Cell Derived Intestinal Organoids - Daoud, Abdelkader; Múnera, Jorge O. (Frontiers in Medicine, 2019)
In recent years, advances in human pluripotent stem cell (hPSC) biology have enabled the generation of gastrointestinal organoids which recapitulate aspects of normal organ development. HPSC derived gastrointestinal organoids are comprised of epithelium and mesenchyme and have a remarkable ability to self-organize and recapitulate early stages of human intestinal development. Furthermore, hPSC derived organoids can be transplanted into immunocompromised mice which allows further maturation of both the epithelium and mesenchyme. In this review, we will briefly summarize work from model systems which has elucidated mechanisms of GI patterning and how these insights have been used to guide the differentiation of hPSCs into organoids resembling small intestine and colon. We will discuss how developmental principles have been used to promote maturation of human intestinal organoids (HIOs) in vitro as well as to introduce an enteric nervous system into HIOs. We will then review how organoids have been used to study human pathogens and how new genetic and bioengineering tools are being applied to organoid research and how this integration has allowed researchers to elucidate mechanisms of human development and disease. Finally, we will discuss remaining challenges in the field and how they can be addressed. HPSC derived organoids are promising new model systems which hold the potential of unlocking unknown mechanisms of human gastrointestinal development and disease.